Mathematics
VicentaWitmer987
18

The work of a student trying to solve the equation 4(2x – 1) = 11 + 3x + 5 is shown below: Step 1: 4(2x – 1) = 11 + 3x + 5 Step 2: 8x – 4 = 16 + 3x Step 3: 8x + 3x = 16 – 4 Step 4: 11x = 24 Step 5: x = 2.18 In which step did the student first make an error and what is the correct step?

+1
(2) Answers
desygirl9801

step3 it suppose to be 8x-3x=16+4

MarlaSom

4(2x - 1) = 11 + 3x + 5 Step 1:  4(2x - 1) = 11 + 3x + 5 Well, this technically isn't really a step, but it's not incorrect. Step 2 : 8x - 4 = 16 + 3x This is correct, because we simplified, as well as added like terms together correctly. Step 3 : 8x + 3x = 16 - 4 This is INCORRECT because when moving variables and integers from either side of the equal sign, you must change the sign! If it was a positive, then you must turn it into a negative, and if it's a negative, you must change it into a positive! Our correct step 3 would be : 8x - 3x = 16 + 4 ~Hope I helped!~

Add answer